Virtual Reality Tourism: Linkage Tourist Intention, Satisfaction, and Quality: Moderating Role of Gender and Visiting Experience - Sobarna, Aditia (Politeknik Negeri Bandung, 2023)
The phenomenon of Covid-19 as the pandemic era changes many factors in our social life, especially in tourist intention, satisfaction, and quality. It is important to be discussed because that phenomenon affects the development of visitor behavioral intention. Based on those backgrounds, this study aims to determine visitor behavioral intention in virtual reality (VR), including the experience with both content and system quality of satisfaction as the determinant factors. The data was obtained from 350 visitors visiting tourist destinations in the greater Bandung region, Indonesia via VR. A self-administered questionnaire was employed using an online survey. The analysis was carried out by using Partial Least Square (PLS) modeling. Results of the analysis show that the experience with content quality has an important role in shaping the behavioral intention of visiting a tourism destination via VR. Next, there is no significant difference in the moderating role of gender and VR experience on the relationships between variables in the behavioral intention model. This study broadens our understanding of the use of the information success model to assess visitor intention in VR tourism and assists practitioners in developing strategies to build and maintain visitor intention to visit and recommend VR tourism.